Sacred and Profane Relations in the Song of Nawwarti Ayy?m? A Study of Roland Barthes' Semiotics in Indonesian Muslim Digital Culture - Najwa Umuriah Lussy, Sitti Wahidah Masnani, Haeruddin Haeruddin Andi Agussalim (Journal of Educational Studies, 2025)
This study examines the sacralization of Arabic-language songs in Indonesian Muslim digital culture, where Arabic is often associated with Islamic religiosity and sacredness. This phenomenon is reflected in the song Nawwarti Ayyami, which is widely used in hadrah performances, majelis sholawat, pesantren activities, and religious social media content despite containing themes of romantic love and emotional intimacy. This study aims to analyze the relationship between the sacred and the profane in the song and to interpret its denotative, connotative, and mythical meanings based on Indonesian Muslim perceptions. A descriptive qualitative approach was employed using Roland Barthes’ semiotic theory. Data were collected through lyric analysis, TikTok and YouTube content, and social media comments representing public reception. The findings reveal that, at the denotative level, the song expresses love and emotional closeness, while at the connotative level it evokes a spiritual atmosphere through the Arabic language, musical intonation, and cultural associations with Islamic symbols. At the mythical level, Arabic is constructed as a representation of sacredness and Muslim religious identity. The study concludes that Nawwarti Ayyami functions not only as popular music but also as a medium for producing religious meaning in contemporary digital culture. This sacralization is reinforced by the Arabic language, its use in religious contexts, and repeated circulation on social media.